Statin use and longitudinal changes in prostate volume; results from the REduction by DUtasteride of prostate Cancer Events (REDUCE) trial - Emma H. Allott; Ilona Csizmadi; Lauren E. Howard; Roberto L. Müller; Daniel M. Moreira; Gerald L. Andriole; Claus G. Roehrborn; Stephen J. Freedland (2019)
To test the association between statin use and prostate volume (PV) change over time using data from the REduction by DUtasteride of prostate Cancer Events (REDUCE) trial, a 4-year randomised controlled trial testing dutasteride for prostate cancer chemoprevention.We identified men with a baseline negative prostate biopsy from REDUCE who did not undergo prostate surgery or develop prostate cancer over the trial period. Men reported statin use at baseline. PV was determined from transrectal ultrasonography performed to guide prostate biopsy at baseline, and 2- and 4-years after randomisation. Multivariable generalised estimating equations tested differences in PV change over time by statin use, overall and stratified by treatment arm. We tested for interactions between statins and time in association with PV using the Wald test.Of 4106 men, 17% used statins at baseline. Baseline PV did not differ by statin use. Relative to non-users, statin users had decreasing PVs over the trial period (P = 0.027). Similar patterns were seen in the dutasteride and placebo arms, although neither reached statistical significance. The mean estimated PV was modestly but significantly lower in statin users relative to non-users in the dutasteride arm at 2-years (4.5%, P = 0.032) and 4-years (4.0%, P = 0.033), with similar (3-3.3%) but non-significant effects in the placebo arm.If confirmed, our present findings support a role for statins in modestly attenuating PV growth, with a magnitude of effect in line with previously reported prostate-specific antigen-lowering effects of statins (~4%). Future studies are needed to assess whether this putative role for statins in PV growth could impact lower urinary tract symptom development or progression.